Home away from home: the impact of work-life balance practices on job satisfaction, employee performance & work-life conflict among resort workers employed in the Maldivian tourism industry - Shaameen, Mohamed (2019)
Despite being the number one contributor to the Maldivian economy, the tourism sector of the Maldives faces difficulties in attracting and retaining locals to work in resorts. One frequently provided explanation for this phenomena is the current HR practices employed in the sector. For instance, unpleasant working arrangements and long working hours are associated with the industry. Engrossed by this phenomena, along with a rising popularity of the notion of work-life balance (WLB) and work-life balance policies in the 21st century, this paper will explore the impact of WLB practices among resort workers employed in the Maldivian tourism industry based on three variables; job satisfaction, perceived employee performance and work-life conflict (WLC). The paper employs a quantitative approach to understanding these relationships. An online survey questionnaire was drafted, which was completed by 202 resort workers currently employed in the Maldivian tourism industry. The results of the survey indicated a statistically significant positive correlation between WLB practices and job satisfaction and employee performance while a significant negative correlation was established between WLB and WLC. It is hoped that the findings of this study would encourage the resort organizations in the Maldives to employ WLB practices that could enhance the quality of life of the employees.